Exact Multiplicity of Solutions for a Class of Singular Generalized One-Dimensional p-Laplacian Problem - Youwei Zhang (Journal of Mathematics)
We describe the existence of positive solutions for a class of singular generalized one-dimensional p-Laplacian problem. By applying the related fixed point theory in cone, some new and general results on the existence of positive solutions to the singular generalized p-Laplacian problem are obtained. Note that the nonlinear term f involves the first-order derivative explicitly.